Longitudinal Changes of Planned Happenstance Skills by Gender, Community Types, and Employment Status in a Sample of College Students in School‐to‐Work Transition. Issue 4 (4th December 2017) - Kim, So Rin; Kim, Boyoung; Yang, NaYeon; Yaung, Huk; Lee, Sang Min
Abstract : This study examined the characteristics of college students who are transitioning from school to work by measuring their mean differences on planned happenstance skills subscales at 3 separate time points. The results indicated that the mean of planned happenstance skills changed across the 3 time points and are somewhat different through demographic factors, such as gender, community types, and employment status. In addition, 2‐way and 3‐way multivariate analysis of variance results showed that the interaction effects of 3 demographic variables on 5 planned happenstance skills were not significant. Practical implications for career counselors are discussed.